Predictions of leachate generation from minerals processing waste deposits - Davies, Graham Mark (Department of Chemical Engineering, 2023)
The minerals processing industry in South Africa produces significant tonnages of waste material which are disposed of commonly in dedicated waste depositories. These deposits pose a potential to pollute the environment if leachate is generated within the deposit and released to the surroundings. Leachate generation is generally investigated using laboratory columnar experiments which attempt to mimic the physical and chemical processes which occur in the deposit. These experiments, termed lysimeter experiments, are time consuming in that they typically last for at least a few months and can last for up to three years. Lysimeter experiments are also costly to conduct. Because of restrictions such as these, relatively few deposits have been characterised to determine the leachate which they generate and thus the risk which they pose to the environment. There is an urgent need to be able to estimate the environmental risks associated with existing waste deposits. The first step towards assessing this risk would be an ability to predict leachate generation within a specific deposit. Such an ability could be used to identify which of the existing deposits produce significant leachate and thus pose a potential hazard to the environment. Equally, if leachate generation from new deposits could be estimated as a function of waste material and characteristics of the waste deposit, this information could be used to improve the engineering design of waste deposits. The work presented in this thesis involved identifying suitable modelling strategies which could be used to determine leachate generation within waste deposits which contain waste material typical of that produced by the minerals processing industry. Two modelling strategies have been investigated. The first modelling strategy involved a macroscopic model in which all effects such as intrinsic chemical kinetics, intra-particle diffusion, external mass transfer and hydrodynamic considerations are lumped into a single parameter. The result of this approach is an effective reaction rate for the release of hazardous constituents from a volume element of the waste deposit. The effective reaction rate is determined by fitting the model to experimental data based on lysimeter tests. The main advantage of this model is that it eliminates the need for a detailed understanding of the individual factors which contribute to leachate generation. This model was investigated both for its inherent simplicity and for use in cases where insufficient information with respect to the intrinsic chemical reaction rates, intra-particle diffusion, external mass transfer or hydrodynamic aspects exist. The main disadvantage of this model is that it has a limited predictive ability in that the individual significance of any one factor which contributes to leachate generation cannot be determined. For this reason a second, more detailed model, termed the heterogenous columnar model, has also been investigated. The heterogenous columnar model describes the release of hazardous constituents at the single particle level and relates this information to the overall leachate generation within the deposit. This is achieved by calculating the release of hazardous constituents from the size distribution of particles to the bulk fluid between these particles. The release of hazardous constituents from individual particles is determined by making use of a particle-scale chemical reaction 'model. This particle-scale model is sufficiently detailed to be able to determine the relative contribution to the overall release of hazardous constituents from the particles of intrinsic chemical kinetics of the reactions to the effects of diffusion of the fluid reagent into each particle. The heterogenous columnar model can also be used to determine whether the effective rate of release of hazardous constituents from the particles (which include intrinsic kinetic and diffusional contributions) or the flow of fluid reagent through the deposit limits the release of hazardous constituents from the deposit. This information can be used to determine the main factors which affect the release of hazardous constituents from waste deposits and can thus be used to improve the design of waste deposits. Probably the most important attribute of the heterogenous columnar model is that methods have been investigated to determine the model parameters from a simple continuously stirred tank reactor (CSTR) type experiment. The ability of the heterogenous columnar. model to predict leaching behaviour has been investigated using data on precious metal leaching found in the literature. The results are encouraging in that the model can accurately predict the leaching behaviour of precious metals. A preliminary investigation into determining suitable particle-scale model parameters for a sample of waste from a CSTR experiment has been conducted. This too has yielded encouraging results. However, the application of using the heterogenous columnar model using these parameters to describe leachate generation within waste deposits or lysimeter experiments still needs to be demonstrated. Once the heterogenous columnar model has been verified against data pertaining to leachate generation from a waste deposit it may start to provide the minerals processing industry with the information which it so desperately requires in order to dispose of wastes in a manner which minimises the impact on the environment.